CREATION OF IN VITRO COLLECTION OF GRAPE HYBRIDS FOR MOLECULAR MARKING AND OBTAINING A HIGHLY PRODUCTIVE VARIETY OF TABLE DIRECTION (Experimental biology, 2023)
The aim of the experiment was to optimize one of the stages of obtaining a new highly productive grape variety – the introduction and propagation of in vitro hybrid shoots. As a result of research, a hybrid fund of table grapes was created in the Kazakh Scientific Research Institute of Fruit and Vegetable Growing. Phenological observations were also carried out on a complex of economically valuable traits, 3 hybrid forms of grapes were identified: KV-2/35, KII-1/29 and DV-10/11, ready for transfer to primary variety testing. It was found that after 3 months of storage of grape cuttings at a temperature of 4° C, the percentage of shoots germination from dormant buds is higher (50.4%) than that of cuttings after 2 months of storage (30.1%). The optimal duration of shoots sterilization sprouted from cuttings in the laboratory room is treatment for 5 minutes in (0.1%) HgCl2 (viability – 27.2%). For shoots germinated in the nursery, the optimal duration of sterilization was treatment for 7 minutes in (0.1%) HgCl2 (viability – 20.6%). No contamination of grapes was detected in vitro after control on a specialized medium 523. For micropropagation, was optimal the nutrient medium: Murashige and Skug with the addition of 30 g/l sucrose, 1 mg/l 6-benzylaminopurine (BAP), 0.1 mg/l indolylbutyric acid, 0.1 ml/l gibberellic acid (GА), 1.5 g/l of Gelrite™, 4 g/l of agar, pH 5.7. It was found that pH 5.7 is optimal for the growth and development in vitro of grape shoots. The addition of the bactericide Plant Preservative MixtureTM to the nutrient medium caused necrosis of test tube plants. An increase in the concentration of BAP to 1.0 mg/l activated the appearance of new shoots. An increase in the concentration of GA and thidiazuron had no effect on the multiplication factor and the quality of the shoots.
Keywords: Grapes, hybrids, selection, variety, optimization of micropropagation, in vitro collection